Improving Descriptive Text Writing Skills of Grade X Students by Using the Complete Sentence Method at SMK Budi Agung Medan - Raun Rouli Lubis; Hetty Zaharani (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to improve the ability of 10th grade students at SMK Budi Agung Medan in understanding and writing descriptive texts through the application of the complete sentence method. Using Classroom Action Research (CAR), this study was conducted in two cycles, each consisting of four phases: planning, action, observation, and reflection. The results showed a significant improvement after the use of the complete sentence method. The students' average score increased from 61.5 in the pre-test to 71.5 in the first cycle, and further increased to 82.66 in the second cycle. These findings indicate that the complete sentence method effectively improves students' comprehension of writing descriptive texts by enabling them to develop more engaging ideas, choose appropriate vocabulary, and construct grammatically accurate sentences.